Cell Structures in Heterologous Anti-Rabies Immunoglobulin Production - S. V. Generalov; E. G. Abramova; A. K. Nikiforov; Zh. V. Matveeva (Проблемы особо опасных инфекций, 2011)
This paper reviews basic modern trends in obtainment of anti-rabies immunoglobulin with enhanced properties. One of these trends is associated with the substitution of organ-tissue antigen by cultural antigen at the stage of producer immunization. Analyzed are the results of research connected with the use of the cell-cultures grown Rabies virus in production of heterologous anti-rabies immunoglobulin. The study testifies of applicability of the transferred Vero cell culture as a substrate for rabies antigen preparation. In addition to this, specified are the advantages of the rabies cultural antigen usage over the organ-tissue one at the stage of hyper-immune serum production.